Enrichment of the fatty acids profile of breads replaced with functional flours blends - Osuna, Mariana Beatriz (2016)
Functional breads constitute an interesting alternative as a vehicle of new essential fatty acid sources. The aim of this study was to improve the fatty acids profile of breads replaced with mixtures of three flours and to analyse the effect of their use on texture parameters, colour and technological characteristics of these products. Wheat flour (WF) was replaced with mixtures of soybean flour (SF), flaxseed flour (FF) and wheat bran (WB). A multilevel factorial design with 3 factors (FF, SF and WB) and 3 levels (0 g/Kg WF – 8 g/KgWF–16 g/Kg WF) were applied; being bread without flour replacement, the control sample. The content of saturated fatty acids (SFA) decreased with increasing concentration of FF, while the content of polyunsaturated fatty acids (PUFA) tended to increase at higher contents of SF and FF. The breads substituted with the highest concentration of FF in mixtures FF+SF or FF+WB showed the highest of n3 fatty acid content. Specific volume of breads with the blends FF+SF and FF+WB showed no significant differences with control (p<0.05). The samples with 16 g/kg FF+16 g/kg WB and with 16 g/Kg FF+8 g/Kg SF were selected for high content n3 and good specific volume. These breads presented harder crumb, less cohesiveness and more chewiness. Colour crumb was more reddish in bread with FF+WB, more yellowish in bread with FF+SF, and both lesser luminous than the control. Although these selected formulations provided breads with high content n3, their crumbs were darker and harder than wheat flour bread.